Impact of Emerging Technologies on Virgin Olive Oil Processing, Consumer Acceptance, and the Valorization of Olive Mill Wastes - Maria Pérez; Anallely López-Yerena; Julián Lozano-Castellón; Alexandra Olmo-Cunillera; Rosa M. Lamuela-Raventós; Olga Martin-Belloso; Anna Vallverdú-Queralt (MDPI AG, 2021)
There is a growing consumer preference for high quality extra virgin olive oil (EVOO) with health-promoting and sensory properties that are associated with a higher content of phenolic and volatile compounds. To meet this demand, several novel and emerging technologies are being under study to be applied in EVOO production. This review provides an update of the effect of emerging technologies (pulsed electric fields, high pressure, ultrasound, and microwave treatment), compared to traditional EVOO extraction, on yield, quality, and/or content of some minor compounds and bioactive components, including phenolic compounds, tocopherols, chlorophyll, and carotenoids. In addition, the consumer acceptability of EVOO is discussed. Finally, the application of these emerging technologies in the valorization of olive mill wastes, whose generation is of concern due to its environmental impact, is also addressed.